Optimization of enzymatic hydrolysis of sago hampas at high substrate load for reducing sugar productions - Mhd Shaifuddin, bin Safiee (Universiti Malaysia Sarawak (UNIMAS), 2016)
There is a wide utilization of agricultural waste as a source for sugar production which later used as substance for value added product. Sago hampas which contains starch and lignocellulose, has shown its capability to be converted into sugar through enzymatic hydrolysis. In this study, the liquefaction and saccharification process of sago hampas with 15 % substrate load was conducted under the pH of 5, temperature of 50C and incuated for about 90 minutes. The Liquozyme and Spirizyme Fuel were used as an enzymes to convert residual starch sago hampas